The Criminalization of Youth in Popular Art in Kenya - Charles, Kebaya (The Journal of Pan African Studies, 2018)
Couched on cultural criminology, this article presents a critical exegesis of how popular cultural productions in Kenya mediate the “criminal” label among youth in Kenya using purposively selected popular arts like pop music, film and parodies. It further examines how branding youth in Kenya as “criminals” is symptomatic of abuse of and excessive use of power by state agents. As such, in this paper, popular arts are viewed as ontological modes of resistance through which youth in Kenya not only voice their displeasure, cope with physical and ideological realities imposed on them by state operatives, but also show an ambivalent sense of morality towards social norms which stifle them. This paper, therefore, contends that these mediated popular cultural texts re-imagine and reconstitute social realities of the “criminal” youth in Kenya.
Keywords: Youth; Popular art; Criminalization